Biomassa, carbono e nutrientes em povoamento de Schizolobium parahyba var. amazonicum em diferentes espaçamentos - Oliveira, Francielle Santana de (2022)
Fast-growing forest species play a key role for Brazilian forest industries, given the growing demand for raw materials for this sector. In this context, the present study aims to verify the influence of planting spacing on aboveground biomass production, carbon stock and nutrients in Schizolobium parahyba var. amazonicum (Huber ex Ducke) Barneby and quantify soil organic carbon and nitrogen. The research was developed in the experimental area of Ifes, in the district of Rive, Alegre, ES, in an area previously occupied with pasture and livestock activity. The stand was implemented in June 2011 with three different planting spacings: 3 m x 3 m, 4 m x 4 m and 5 m x 5 m. Deformed soil samples were collected at depths 0-20; 20-40; 40-60; 60-80 and 80-100 cm, at 8.2 years of age of the stand, to evaluate fertility, organic carbon and total soil nitrogen. To obtain the metric variables of the forest inventory at 8.3 years of age of the stand was carried out. Biomass and carbon content were obtained using the direct method in the stem, bark, thin branches, thick branches and leaves compartments, in which the content was quantified and the stock of nutrients (N, P, K, Ca, Mg), calculated nutrient use efficiency (EUN) and number of cuts (NC) to evaluate biomass harvesting scenarios. The maximum value of CTC (t) for the densest spacing was 1.9 and 2.3 times greater than the intermediate spacing and the least dense. The lowest mean values for soil density (Ds) occurred in the surface horizons, with a general mean of 1.33 g cm- ³. C stocks in the 3 m x 3 m and 4 m x 4 m spacing in the order of 34.63 and 36.90 Mg ha1 , for the 0-20 cm layer, corresponding to an increase of 13.8 and 21.3 % compared to 5 m x 5 m spacing. The total production of biomass and C stored in the trees was 55.9 Mg ha-1 and 24.6 Mg ha-1 . The higher planting density promoted higher biomass production and stock of C (Mg ha-1 ) and nutrients in the plants. The accumulation of nutrients more accentuated in the bole, except for Ca, which accumulates in greater proportions in the bark and branches. The trend of nutrient accumulation in the biomass was: stem > thick branches > thin branches > bark > leaves. Planting spacings did not interfere with EUN patterns. Among the nutrients evaluated, Ca presented a low EUN when compared to P and Mg, which presented higher EUN in the production of all biomass components. For the harvest scenario, N, P and K are the main nutrients that may limit the productivity of the stand to conduct new cycles. Therefore, to promote nutritional sustainability, it is recommended to harvest only the trunk wood.